Answer:
76
Step-by-step explanation:
1.) 8 x 8 =64
2.) 12 + 64 =76
The answer is x = 10, y = 10.
Step 1: rearrange the second equation for y.
Step 2: substitute y from the second equation into the first equation.
Step 3. Calculate y.
Step 1.
<span>The second equation is: 6x + 3y = 90
Divide both sides of the equation by 3:
(6x + 3y)/3 = 90/3
6x/3 + 3y/3 = 30
2x + y = 30
Rearrange the equation:
y = 30 - 2x
Step 2.
</span>Substitute y from the second equation (y = 30 - 2x) into the first equation:
<span>15x + 9y = 240
15x + 9(30 - 2x) = 240
15x + 270 - 18x = 240
15x - 18x = 240 - 270
-3x = -30
x = -30/-3
x = 10
Step 3.
Since </span>y = 30 - 2x and x = 10, then:
y = 30 - 2 * 10
y = 30 - 20
y = 10
Answer:
36
Step-by-step explanation:
Compare what you have to the square ...
(a +b)^2 = a^2 +2ab +b^2
Your "a" is √(25x^2) = 5x
Your "2ab" is -60x. Since you know "a", you can find "b".
2ab = -60x
2(5x)b = -60x . . . . . . . substitute for "a"
b = -60x/(10x) = -6
Then the missing term is b^2 = (-6)^2 = 36.
Your trinomial is ...
25x^2 -60x +<u>36</u>
Answer:
x = 18/5
Step-by-step explanation:
7x + 4 = 2x+ 22
5x = 18
x = 18/5